SABIC - Petrochemical Manufacturing Company - Al Mudhayan, Alaa; Alajmi, Rakan; Betancur, Susana Lemus; Al Shamlan, Ali Ahmad (Asia Pacific Journal of Management and Education (APJME), 2019)
SABIC is a global company in the field of the production of various chemicals. Located in more than 50 countries and headquartered in Riyadh, Saudi Arabia. Divided into 4 different unis; petrochemicals, specialties, agricultural nutrients and minerals. SABIC seeks to be the most innovative petrochemical company in the world, as it does its best to turn ideas into reality, and strives to improve manufacturing processes and innovate new technologies for competitive advantage to improve their quality. The purpose of this paper is to explain and understand how SABIC grew and expanded, how it became a global company with prencese in more than 50 countries. What are the strategies for the expansion and the importance of innovation in its success?